Analisis Faktor-Faktor yang Mempengaruhi Ketahanan Pangan Rumah Tangga Komunitas Sagu di Desa Puulowaru - Asmarani, Andi Adinda; Ma'mun, Sitti Rahma; Nurcayah; Asis, Patta Hindi (Fakultas Pertanian Universitas Muhammadiyah kendari, 2025)
The purpose of this study was to determine the situation of household food security in Prowal Village, Besulutu District, Konawe Regency, and to identify factors that influence household food security when consuming sago. The study was conducted in Pulowaru Village, Besulutu District, Konawe Regency. The location was selected intentionally (purposive). This survey was conducted for approximately two months from August to September 2022. The number of samples used was 60 respondents using the simple random sampling method. The data obtained included primary data and secondary data. The analysis used was multiple linear regression analysis. The results of the analysis showed that variables such as age, house area, income, and consumption had a significant effect on food access. The coefficient of determination showed 0.992, which means that age, house area, income and consumption affect food access at 99.2% of food security. 0.8% is influenced by other factors not included in this study.